SOME SPECIFICATIONS ON THE ANALYSIS OF ὡς AS A FINAL CONJUNCTION IN HOMER - Redondo, Jordi (AADEC - UNL, 2018)
It is a commonplace in the field of the Ancient Greek syntax to refer to the subordinating conjunction ὡς as a polyfunctional one. In this paper we will check its final use in Homer; first of all we will show in a rigorous way our data, and a second step will give us the occasion to contrast them with the theories on this construction.